Agent-Based Modeling of Employee Protection-Oriented Safety Proactivity Behaviors at Small Scale Enterprises. (19th May 2019) - Wang, Qiwei; Curcuruto, Matteo; Mei, Qiang; Liu, Suxia; Zhou, Qiaomei; Zhang, JingJing
Abstract : Although the safety production level at small scale enterprises is important for business success, critical safety interactions among the enterprises, its employees, the public, and the government have not been explained well in the literature. To address this gap, a bottom-up method of agent-based modeling is applied here that includes these key stakeholders. The study illustrates how employee protection-oriented safety proactivity behaviors, including whistleblowing and public exposure, can impact the safety production level at small scale enterprises, which are also watched by the public and regulated by the government. The results confirm that protection-oriented safety proactivity behaviors have a significant impact on the safety production levels at small enterprises through the interactions among multiple agents. The model results are validated using an employee questionnaire. The recommendation is for employees to encourage protection-oriented safety proactivity behaviors to improve safety production levels and for the public and the government to provide additional safety support.